Fabrication and evaluation of the mechanical behavior of geopolymer compounds using waste from the mining and construction industry - Huamán-Mamani F.A. (2021)
Geopolymers are lately being considered a group of revolutionary materials, due to their good mechanical properties, chemical stability, fire resistance and diversity of applications where they can be used. For the synthesis of geopolymers, a great variety of types of natural and artificial raw materials (residues from other industries) can be used, which allows obtaining materials with very specific applications. Two of the most important industries in Peru are also those that generate greater environmental degradation, mainly due to the waste they generate. The mining industry has a negative impact on the environment, generating a large amount of inorganic waste, while the construction industry does the same, generating large amounts of demolition waste. Both, mining and demolition waste, constitute a serious environmental problem, since currently they are only deposited without any alternative use. Therefore, our research proposes the use of geopolymeric technology for the use of mining and demolition waste in the manufacture of geopolymeric concrete with mechanical strengths similar to that of Portland cement concrete. © 2021 Institute of Physics Publishing. All rights reserved.